Consumer Engagement in Social media: The Impact of Influencer Marketing on Millennials’ Cosmetic Purchasing Behavior in China - Liang, Yuan (2019)
An emerging marketing strategy, influencer marketing, has become rapidly popular in the marketing field in recent years. It relies on the appeal of Internet celebrities (opinion leaders) among fans to stimulate or influence consumers’ cognition or attitude towards the brand, to achieve the corresponding profit target. As social media has become a more integrated part of people’s lives, marketers need to pay particular attention to how to respond to the growth of social media users, especially millennials, who have a lot of buying power. At the same time, this generation has a richer experience on the Internet and is accustomed to listening to the opinions of opinion leaders to assist in their own consumption decisions. Indeed, there is now evidence that influencer marketing could have a huge impact on the purchasing behavior of some consumers. However, the impact on millennials remains to be explored. This dissertation conducts an empirical study on 142 millennials based on the ELM model. Linear regression analysis and factor analysis are mainly used to explore the relationship between potential variables, to verify whether influencer marketing has an impact on consumers’ purchasing behavior and brand equity in the cosmetics industry. According to various data analysis, the conclusions about the relationship between influencers marketing and the purchasing behavior of cosmetics by millennials were obtained and the research findings were explained. Finally, by dissecting the main findings of these studies, it is then proposed to some brands or cosmetics companies to rationalize the future implementation of the influencer marketing strategy.